2012
DOI: 10.1097/nrl.0b013e318247b9a5
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antithrombotic Treatment With Aspirin and Clopidogrel for Patients With Capsular Warning Syndrome

Abstract: Capsular warning syndrome is characterized by recurrent transient ischemic attacks and is caused by microthrombosis or hypoperfusion of small-sized vessels. The pathophysiological basis of this syndrome is not well understood and currently a consensus has not been reached on its optimal treatment. In this study, we present 2 cases with favorable clinical outcomes after combined antithrombotic treatment with loading doses of clopidogrel and aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
0
16
0
3
Order By: Relevance
“…There was no strong evidence for the efficacy of anticoagulant therapy in the acute phase of CWS. There had been case series suggesting that double antiplatelets (aspirin add clopidogrel) might be beneficial, similar to the effect seen in acute coronary syndromes [7,27,28]. In a case series including two patients with CWS, it was reported that following the start of double antiplatelets, there was no progression of symptoms.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…There was no strong evidence for the efficacy of anticoagulant therapy in the acute phase of CWS. There had been case series suggesting that double antiplatelets (aspirin add clopidogrel) might be beneficial, similar to the effect seen in acute coronary syndromes [7,27,28]. In a case series including two patients with CWS, it was reported that following the start of double antiplatelets, there was no progression of symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…Despite various treatments being available and used, it was unclear whether these treatments alter the natural course of the syndrome. Intravenous thrombolysis, double antiplatelet therapy, single antiplatelet therapy, anticoagulants, vasopressors had been used to treat patients with CWS [1,4,5,7,[9][10][11][12][13][20][21][22][23][24][25][26][27][28], it remains uncertain whether any of these therapies were able to change the progression of the syndrome. There was no strong evidence for the efficacy of anticoagulant therapy in the acute phase of CWS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kapsüler uyarı sendromunda da iskemik olay riskinin kanama riskinden fazla olması nedeniyle bu tedavinin kapsüler uyarı sendromlu vakalarda da uygun olabileceği düşünülmüştür. Asil ve arkadaşları kapsüler uyarı sendromu tanısı konan 2 vakayı 300 mg klopidogrel ve aspirin ile tedavi etmiş ve olumlu sonuçlar bildirmişlerdir (8). Bu tedaviden fayda gören birçok vaka bildirilmiştir.…”
Section: Olguunclassified